2010
DOI: 10.1097/qai.0b013e3181bc4869
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, Contraceptive Use, and HIV Acquisition in HPTN 039: Relevance for HIV Prevention Trials Among African Women

Abstract: Background-Biomedical HIV prevention trials enroll sexually active women at risk of HIV and often discontinue study product during pregnancy. We assessed risk factors for pregnancy and HIV acquisition, and the effect of pregnancy on time off study drug in HPTN 039.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
78
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 16 publications
13
78
3
Order By: Relevance
“…Twenty eligible reports were included in the previous review [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], and out of 400 references retrieved in our updated search (Fig. 1), we identified one new eligible subanalysis of a previously included study [61] and two new eligible studies [62,63].…”
Section: All Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty eligible reports were included in the previous review [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], and out of 400 references retrieved in our updated search (Fig. 1), we identified one new eligible subanalysis of a previously included study [61] and two new eligible studies [62,63].…”
Section: All Included Studiesmentioning
confidence: 99%
“…Among 22 included studies (represented by 23 reports), 18 included estimates specific to OCs [41-,47-53,57-60,62,63], 16 included estimates specific to injectable contraception [41,42,[48][49][50][51][52][53][54][55][57][58][59][60]62,63], and two did not distinguish between methods of HC although the investigators noted that most of the HC users used injectables [46,56]. No eligible studies assessed the contraceptive patch, ring, combined injectable, or levonorgestrel IUD.…”
Section: All Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review [67], four of nine studies considered informative but with important limitations reported a 1.5 to 2.2 times increased risk of HIV acquisition in women using injectable contraception(DMPA) [3,28,56,87]. The remaining five studies of injectable contraception in the review [39,57,62,71] reported no statistically significant association with risk of HIV acquisition. In the same review [67], only one study reported increased risk of acquisition resulting from the use of oral contraceptive pills (OCPs).…”
Section: Introductionmentioning
confidence: 99%